Investigation Of University Students' Overall Quality Of College Life And Their Satisfaction With This Life Terms Of Their Genders And Departments - Kadir Pepe; Rabia Özkurt; Osman Dalaman (Selcuk University, 2020)
The current study was conducted to investigate university students' life quality and life satisfaction in the campus. The study was designed in the survey model. The population of the study is comprised of the students attending the Physical Education and Sports School, Faculty of Economics and Administrative Sciences, Faculty of Health Sciences and Faculty of Education in the central campus of Burdur Mehmet Akif Ersoy University. The sample consists of 400 students selected from among the population through random sampling. The data were collected through the questionnaire method. As the questionnaire, "The University Life Quality Scale" adapted to Turkish by (13) was used. From this scale, the overall life quality and overall life satisfaction dimensions were taken. The Cronbach's Alpha reliability coefficient was calculated to be 0.85 for the overall life quality dimension and 0.83 for the overall life satisfaction dimension. The questionnaire was administered to the students through face-to-face method. A total of 400 students (212 females and 188 males) responded to the questionnaire. In order to analyze the collected data, percentages (%) were calculated and Independent Samples T Test and Kruskal-Wallis Test, Bivariate Correlation were used. In the determination of the differences between the variables, 0.05 was taken as the confidence interval. The obtained findings have revealed that the students' overall life quality and life satisfaction in the campus mean scores are low, that while their mean scores do not vary significantly by gender, their overall life quality mean scores vary significantly depending on the faculty they attend (p lt;0,05). As a result, it can be said that the participating students' overall life quality and life satisfaction in the campus mean scores are low.